Comparison of humeral rotation co-activation of breast cancer population and healthy shoulders. (August 2016) - Brookham, Rebecca L.; Dickerson, Clark R.
Abstract: Upper limb morbidities are common amongst the breast cancer population (BCP) and have a direct impact on independence. Comparing muscle co-activation strategies between BCP and healthy populations may assist in identifying muscle dysfunction and promote clinical interpretation of dysfunction, which could direct preventative and therapeutic interventions. The purposes of this study were to define humeral rotation muscle co-activation of a BCP and to compare it with a previously defined co-activation relationship of a healthy population. Fifty BCP survivors performed 18 isometric internal and external rotation exertions at various postures and intensities. Surface and intramuscular electrodes recorded shoulder muscle activity. BCP co-activation was predicted at r 2 = 0.77 during both exertion types. Humeral abduction angle and task intensity were important factors in the prediction of co-activation in both populations. Comparisons made between populations identified differing muscle strategies used by BCP to maintain postural control. Compared to healthy co-activation, the BCP demonstrated greater activation of internal (IR) and external rotator (ER) type muscles during their respective rotation type. The BCP demonstrated increased (⩾8.7%) activation of pectoralis major. This study has provided insight into how BCP muscles compensate during dysfunction. Continued advancement of this knowledge can provide more understanding of dysfunction, promote generation of evidence-based therapies, and can be useful in biomechanical modeling.